The influence of cross-language similarity on within- and between-language Stroop effects in trilinguals - van Heuven, Walter J.B.; Conklin, Kathy; Coderre, Emily L.; Guo, Taomei; Dijkstra, Ton (Frontiers, 2011)
This study investigated effects of cross-language similarity on within- and between-language Stroop interference and facilitation in three groups of trilinguals. Trilinguals were either proficient in three languages that use the same-script (alphabetic in German–English–Dutch trilinguals), two similar scripts and one different script (Chinese and alphabetic scripts in Chinese–English–Malay trilinguals), or three completely different scripts (Arabic, Chinese, and alphabetic in Uyghur–Chinese–English trilinguals). The results revealed a similar magnitude of within-language Stroop interference for the three groups, whereas between-language interference was modulated by cross-language similarity. For the same-script trilinguals, the within- and between-language interference was similar, whereas the between-language Stroop interference was reduced for trilinguals with languages written in different scripts. The magnitude of within-language Stroop facilitation was similar across the three groups of trilinguals, but smaller than within-language Stroop interference. Between-language Stroop facilitation was also modulated by cross-language similarity such that these effects became negative for trilinguals with languages written in different scripts. The overall pattern of Stroop interference and facilitation effects can be explained in terms of diverging and converging color and word information across languages.